Determinan Factor that Affect The Intention to Use Sharia Financing: Piety as a Moderator - Eva Maulani; Imronudin Imronudin (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
This study aims to determine the influence of the social environment, religious Awareness, profit margins, and ease of intention to use Sharia financing by using Piety as a moderation variable. The research method used is the quantitative method. The number of samples in this study was 94.04, rounded up to 100 respondents. Question indicators are measured using the Likert scale, which has five levels of preference, each of which is scored from 1 to 5. The results of the research obtained were processed using Smart-PLS. Based on the results of the analysis of research results using Smart-PLS, it shows that 1) The social environment does not have a positive and insignificant effect on the intention to use Islamic financing; 2) Religious Awareness has a positive and significant effect on the intention to use sharia financing; 3) Profit margins have no positive and insignificant effect on the intention to use financing; 4) Ease has a positive and significant influence with the intention to use Islamic financing that has significant results; 5) Piety has no positive and insignificant effect with the intention of using sharia financing whose results are insignificant; 6) Moderation Effect 1 has no positive and insignificant effect on the intention to use Islamic financing; 7) Moderation Effect 2 has no positive and insignificant influence on the intention to use Islamic financing; 8) Moderation Effect 3 has no positive and insignificant influence on the intention to use Islamic financing; 9) Moderation Effect 4 has no positive and insignificant influence on the intention to use Islamic financing.